Pengaruh Iklan Instagram, Gaya Hidup, dan Brand Awareness Terhadap Minat Beli Produk Selkom-C - Philips Pangestu; Faturohman; Theresia Pradiani (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
In this era of digitalization, many Indonesians are using Instagram as their main choice of social media. Hence, many companies are using Instagram Ads as one of their marketing strategy. Lifestyle is also affected due to the COVID-19 Pancemic effect. Many more people are becoming aware of the importance of health and showing it by consuming vitamin C as their lifestyle. In choosing which vitamin C to consume, brand awareness holds an important role. Selkom-C is one of the brands of vitamin C that experience a sales increase after the pandemic COVID-19. The purpose of this study was to determine: 1) the impact of Instagram advertisement on purchase intention, 2) the impact of lifestyle on purchase intention, 3) the impact of brand awareness on purchase intention. This study is a quantitative research that uses a questionnaire as the data collecting method. This study uses a purposive sampling technique towards the citizens of East Java who are above 17 years old and have seen Selkom-C’s Instagram advertisement. The sample population is 100 respondents and the data result was processed through the SPSS 20 software. The outcome of this study shows that: 1) there is a possitive and significance impact of Instagram Advertisement towards purchase intention. this is reflected in the current Hashtag (#vitaminmasakini) which is suitable for Selkom-C Instagram ads which are always current 2) there is a possitive and significance impact of Lifestyle towards purchase intention, this is reflected in the lifestyle of the respondents indicating that a healthy life is very important 3) there is a possitive and significance impact of Brand Awareness towards purchase intention, which is reflected in the Selkom-C brand that respondents have heard of